Změna palivové základny uhelného kotle - Kallas, Miloš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Diplomová práce se zabývá změnou palivové základny uhelného kotle z důvodu snížení emisí CO2 a jeho tepelným přepočtem. V úvodní části je proveden výpočet spalovací komory. Poté následuje přepočet teplosměnných ploch. Je kladen důraz na zachování stávajících parametrů páry.

This thesis deals with the change of the fuel base of a coal boiler due to the reduction of CO2 emissions and its thermal recalculation. In the first part, there is implemented calculation of the combusting chamber. This is followed by the recalculation of the heat transfer surfaces. The emphasis is placed on the preservation of the exsiting steam parametrs.
Changing the fuel base of the coal boiler
Keywords: Parní kotel; stechiometrické výpočty; tepelný výpočet; přehřívák; výparník; ekonomizér; Steam boiler; stoichiometry; thermal calculation; superheater; evaporator; economizer.